Chaetothylax rzedowskii (Acanthaceae), una especie nueva de Chiapas, México - Acosta Castellanos, Salvador (Instituto de Ecología, A.C., 1989)
A new species of Chaetothylax, an exclusively American genus, is described and its affinities with C. rothschuhii Lindau, a Central America species, are discussed. Its pollen grains are studied under the scanning eletron microscope.